An Assessment of the Investment Climate in Uganda - World Bank (World Bank, Washington, DC, 2013)
The goal of the Investment Climate Assessment (ICA) of Uganda is to evaluate the investment climate in Uganda in all its operational dimensions and to promote policies to strengthen the private sector and encourage broad-based economic growth. Sustained improvements in living standards depend on broad-based growth. Growth will only occur, however, if firms improve their productivity by investing in human and physical capital and by increasing their technological capacity. But firms will only do this when the investment climate is favorable. Throughout the report, Uganda's investment climate is compared to the investment climates of three groups of countries: 1) nearby countries in East Africa (Kenya, Tanzania, Rwanda and Burundi); 2) middle-income countries in Sub-Saharan Africa (SSA) that have successfully diversified out of primary production into other sectors (Mauritius, South Africa and Swaziland); and 3) several fast growing countries in East Asia that have also successfully diversified out of primary production into export-oriented manufacturing (China, Malaysia, and Thailand). Finally, infrastructure appears to be a more serious problem for microenterprises than for Small, Medium-sized or Large Enterprise (SMLEs). Although the differences in the number of outages and losses during transportation between registered microenterprises, unregistered microenterprises, and SMLEs were small and statistically insignificant, access does appear to be a more serious problem for microenterprises.